SOME FEATURES OF TOPONYMY OF THE REPUBLIC OF KARAKALPAKSTAN - Seytniyazov K. M. (European Science Publishing, 2024)
The article examines some patterns of names and territorial diversity of toponyms, as well as their significance of specific, political and practical significance. Also, on specific examples, their origin and etymology of some toponyms are studied.
Keywords: toponyms, ethnonyms, hydronyms, oikonyms, geographical terms, hydronymic terms, geographical objects, floristic topotherms, social need, address function.